The Influence of Service Quality and Price on Visitor Satisfaction of Indonesian Indah Mini Park Bird Park - Friska Hotnida Saragih, Friska Hotnida Saragih; Kwaryanto Rohmawan; Nurminingsih; Robert Siregar (Journal of Entrepreneur and Business, 2023)
Indonesia is a religion, ethnicity, and culture, each of which has a very special tourism attraction. So many people love to travel. In addition to being able to relieve fatigue all day at work, you can also gather with family tours that provide good benefits and will be visited by many people. This research uses quantitative methods, this research was conducted in Bird Park (beautiful Indonesian mini park) ). In this study using a sample of 100 respondents from visitors, the data was analyzed using Structural Equation Modeling (SEM). The results of this study are (1) service quality has a significant effect on visitor satisfaction. (2) price has no significant effect on visitor satisfaction (3) service quality has a significant effect on ticket prices for Taman Mini Indonesia Indah Bird Park. Keywords: service quality, price and visitor satisfaction